2012
DOI: 10.1016/j.jss.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Treatment Attenuates MAP Kinase Pathway Activation and Pulmonary Inflammation Following Hemorrhagic Shock in a Rodent Model

Abstract: Background Hemorrhagic shock activates cellular stress signals and can lead to systemic inflammatory response, organ injury, and death. We have previously shown that treatment with histone deacetylase inhibitors (HDACIs) significantly improves survival in lethal models (60% blood loss) of hemorrhage. The aim of the current study was to examine whether these protective effects were due to attenuation of mitogen activated protein kinase (MAPK) signaling pathways, which are known to promote inflammation and apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
1
33
1
Order By: Relevance
“…Thus, Aza+TSA might be considered as putative anti-inflammatory treatment that modulates LPS-stimulated inflammatory responses and activates an array of key anti-inflammatory signaling pathways. Recent data indicate that members of the MAPK family are involved in modulating mRNA stability and/or translation of several genes (Kochanek et al, 2012;Rajasingh et al, 2006). Our data show that treatment with Aza+TSA abrogated the LPS-TLR4-MAPK pathway, which initiated an inflammatory cascade, and is known to potentiate apoptotic signals within the macrophages.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Thus, Aza+TSA might be considered as putative anti-inflammatory treatment that modulates LPS-stimulated inflammatory responses and activates an array of key anti-inflammatory signaling pathways. Recent data indicate that members of the MAPK family are involved in modulating mRNA stability and/or translation of several genes (Kochanek et al, 2012;Rajasingh et al, 2006). Our data show that treatment with Aza+TSA abrogated the LPS-TLR4-MAPK pathway, which initiated an inflammatory cascade, and is known to potentiate apoptotic signals within the macrophages.…”
Section: Discussionmentioning
confidence: 52%
“…We and others and have shown previously that members of the MAPK family are involved in modulating mRNA stability and/or translation of several pro-inflammatory genes (Kochanek et al, 2012;Rajasingh et al, 2006). Studies have shown that activation (i.e.…”
Section: Aza+tsa Treatment Suppresses Hur Expression and P38mapk Actimentioning
confidence: 91%
See 1 more Smart Citation
“…Others have found that VPA can reduce lung inflammation in acute lung injury and hemorrhagic shock models. 23,24 This difference may reflect the level of inflammation in chronic disease and the treatment regimen used. We did however find a strong therapeutic effect on airway remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…DSM-RX78 and EFB-1 were synthesized as described previously. 16 Partition Coefficients (log P ) of PDE4 Inhibitors Octanol or squalene (1 ml) including predetermined concentrations of DSM-RX78, EFB-1, or their metabolite, SMP-3 ( Fig. 1), was mixed with water (1 ml).…”
Section: Methodsmentioning
confidence: 99%